MENINGKATKAN KEMAMPUAN BERORGANISASI MELALUI PERANCANGAN PROPOSAL YANG EFEKTIF DI SMK SASMITA JAYA 1 - Permana, Yudisti Prayigo; Indayani, Indayani; Hasanah, Sari Nida’ul; Yulianti, Yulianti; Yanti, Yuli (Indonesian Collaboration Journal of Community Services (ICJCS), 2024)
Organizational ability is one of the soft skills that is important for vocational school students to prepare for the world of work. One way to improve organizational skills is through designing effective proposals. This research aims to improve the organizational skills of class X students at SMK Sasmita Jaya 1 through designing effective proposals. This research uses a quantitative method with a pre-test and post-test design. The research sample was 30 class X students of SMK Sasmita Jaya 1 who were chosen randomly. The research instrument used was a questionnaire consisting of 10 questions. The data analysis technique used is the Mc Nemar Test. The results of the research showed that there was a significant increase in the organizational abilities of class Effective proposal design can improve the organizational skills of class X students at SMK Sasmita Jaya 1